Pediococcus acidilactici Promotes the Longevity of C. elegans by Regulating the Insulin/IGF-1 and JNK/MAPK Signaling, Fat Accumulation and Chloride Ion - Hu, Rui; Zhang, Yong; Qian, Weiyi; Leng, Yan; Long, Yan; Liu, Xinjie; Li, Jinping; Wan, Xiangyuan; Wei, Xun (Frontiers in Nutrition, 2022)
Probiotics are known to contribute to the anti-oxidation, immunoregulation and aging delay. Here, we investigated the extension of lifespan by fermented pickles-origin Pediococcus acidilactici (PA) in Caenorhabditis elegans (C. elegans), and found that PA promoted a significantly extended longevity of wild-type C. elegans. The further results revealed that PA regulated the longevity via promoting the insulin/IGF-1 signaling, JNK/MAPK signaling but not TOR signaling in C. elegans, and that PA reduced the ROS levels and modulated expression of genes involved in fatty acids uptake and lipolysis, thus reducing the fat accumulation in C. elegans. Moreover, this study identified the nrfl-1 as the key regulator of the PA-mediated longevity, and the nrfl-1/daf-18 signaling might be activated. Further, we also highlighted the roles of one chloride ion exchanger gene sulp6 in the survival of C. elegans and other two chloride ion channel genes clh1 and clh4 in the prolonged lifespan by PA-feeding through modulating expression of genes involved in inflammation. Therefore, these findings reveal the detailed and novel molecular mechanisms on the longevity of C. elegans promoted by PA.